The relationship between holistic care and therapeutic healing: its implications to nursing education and service - Tomas, Maria Anita S.
This is a study on the relationship between holistic care and therapeutic healing. The premise rests on the holistic care of the total person who at the time of sickness is bodily afflicted and concomitant to that the psycho-socio-spiritual aspect of man is also affected. It goes with a saying that the nurse should have a deeper understanding that the human being is composed of body, soul and spirit. The purpose of this study is to develop an empathetic understanding of caring for the sick which involves the inner healing. The study attempts to answer these questions: 1. Does holistic care promote therapeutic healing? 2. Are there relevant implications of this study to nursing education and service? Holistic care involves deliberate, rational and knowledgeable acts of assistance to the patient, as well as feelings of tenderness and concern conveyed to her for the total development of her whole person which includes the physical, psychosocial, curative, and spiritual elements of care. Therapeutic healing is a process or status in the various significant health conditions of the patients whereby positive consequences occur or are achieved towards her comfort, well-being and total development.